Transformations and Transfer: Preschool Children Understand Abstract Relations and Reason Analogically in a Causal Task. Issue 6 (2nd September 2020) - Goddu, Mariel K.; Lombrozo, Tania; Gopnik, Alison
Abstract : Previous research suggests that preschoolers struggle with understanding abstract relations and with reasoning by analogy . Four experiments find, in contrast, that 3‐ and 4‐year‐olds ( N = 168) are surprisingly adept at relational and analogical reasoning within a causal context. In earlier studies preschoolers routinely favored images that share thematic or perceptual commonalities with a target image ( object matches ) over choices that match the target along abstract relations ( relational matches ). The present studies embed such choice tasks within a cause‐and‐effect framework. Without causal framing, preschoolers strongly favor object matches, replicating the results of previous studies. But with causal framing, preschoolers succeed at analogical transfer (i.e., choose relational matches). These findings suggest that causal framing facilitates early analogical reasoning.